Banana genotype composition along the Uganda-Democratic Republic of Congo border: a gene pool mix for plantain and highland bananas: In: Banana systems in the humid highlands 22 of Sub-Saharan Africa (eds G. Blomme, P. van Asten and B. Vanlauwe) - Karamura, D.; Ocimati, W.; Ss, R.; Jogo, W.; Walyawula, S.; Karamura, E.B. (CAB International, 2013)
Landraces contain many genotypes, which makes them a good source of genes for crop improvement and hence provide an incentive to conserve them. Banana sampling and collection were carried out along the Uganda–Democratic Republic of Congo (DR Congo) border, which is home to the largest in situ diversity of the Musa AAA Lujugira-Mutika subgroup (Uganda) and the Musa AAB Plantain subgroup (DR Congo). The objectives of the collecting mission were to explore Musa genetic resources along the border districts, sample and collect unique Musa germplasm and assess the cross-border genotype diversity.